DESIGN OF A 1 KG GOLD SMELTING FURNACE USING PERTALITE FUEL - Darmawan, Darmawan; Mujiarto, Mujiarto; Wagiman, Acep (PT Altin Riset Publishing, 2025)
The objective of this study is to design and test a small-scale gold melting furnace with a capacity of 1 kg that is capable of producing high enough temperatures to melt gold efficiently. The gold smelting process requires a significant amount of energy, making the selection of the appropriate furnace type and accurate temperature control crucial for optimizing energy efficiency and smelting results. This study involves the design of an induction heating-based smelting furnace, chosen for its efficiency in rapid and uniform heating. The melting process was carried out by heating the gold ore until it reached the melting point of gold at approximately 1064°C, while measuring the energy required during the process. The results of the study indicate that the total energy required to melt 1 kg of gold is approximately 197,531 joules.